Screening on antioxidant activities of by – products from vegetables and fruits in Vietnam and applying for shrimp cold storage - Phan Thi Anh Dao (Journal of Technical Education Science, 2018)
We have carried out studying for antioxidant activity of 58 extracts prepared from vegetables and fruits in Viet Nam by three methods including DPPH and H2O2 scavenging activity assays and determination of total flavonoid content (TFC). Ethanol extract of Tamarind seed (NTBT-17), Grape seed (NTBT-19) and Mangosteen peel (TNB-10) showed high amount of TFC which is 848.8, 655.9 and 422.9 mgQE/100g, respectively. In addition, NTBT-17, NTBT-19 and mango seed (TNB-11) exhibited strong activity with the following IC50 (DPPH method) values: 6.91, 2.10, 1.84 µg/mL, respectively. Basing on the H2O2 assay, TNB-10 has the lowest IC50 value of 104.2 µg/mL. Therefore, TNB-10 extract was used as a natural antioxidant food preservative for white shrimp (Litopenaeus vannamei) cold storage at 2°C and tested sensory evaluation of melanosis development and lipid peroxidation inhibition assay (TBARs). Shrimps treated by TNB-10 had gray values and TBARs values lower than the control samples (treated by water) and shrimps treated by sodium metabisulfite (SMS). According to the identification of constituents in TNB-10 by HPLC-ESI-MS, nine antioxidant compounds namely, α-mangostin, β-mangostin, γ-mangostin, 8-dexoxygartanin, garcinone B, garcinone C, garcinone D, 9-hydroxycalabaxanthone, and garcinmangosone C were found. These results suggested that mangosteen peel extract was able to slow down oxidation process of fat and melanosis development in white shrimp during the cold processing.